Design of Rice Farming Monitor Information System - Senny Luckyardi; S Hasya; I Fadhillah; M Azis; Raiswati Untsa Mega (International Journal of Education, Information Technology, and Others, 2021)
This study aims to design an information system that can monitor rice yields in each area in West Java. To support this research, the descriptive method was used through observation and supported by literature studies. The results showed that an information system for harvest monitoring can be the alternative solution for the government and farmers themselves. It helps the government to provide real solutions to farmers in case of a decrease in rice yields. In addition, the monitoring system may help the farmers to prevent loss. For the long-term purpose, it is expected that rice yields can always be stable in every harvest because an application information system monitors it. The website-based application to monitor agricultural products is considered effective. This research is expected to give the government input to shift from manual system to the utilization of information system.